2023
DOI: 10.1002/bit.28513
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular accumulation of c‐di‐GMP and its regulation on self‐flocculation of the bacterial cells of Zymomonas mobilis

Abstract: Zymomonas mobilis is an emerging chassis for being engineered to produce bulk products due to its unique glycolysis through the Entner–Doudoroff pathway with less ATP produced for lower biomass accumulation and higher product yield. When self‐flocculated, the bacterial cells are more productive, since they can self‐immobilize within bioreactors for high density, and are more tolerant to stresses for higher product titers, but this morphology needs to be controlled properly to avoid internal mass transfer limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…This and previous studies had shown that the A526V mutation in ZMO1055ZM401 maintains cell aggregation and the intracellular cyclic di-GMP concentrations to a greater extent (Cao, Yang et al 2022, Li, Xia et al 2023. The conservation of alanine at position 526 in subclass ZMO1055 GGDEF-EAL domain proteins indicates that alanine is important for functionality of the EAL domain.…”
Section: Amino Acids At Position 526 Differentially Affect the Appare...supporting
confidence: 72%
See 4 more Smart Citations
“…This and previous studies had shown that the A526V mutation in ZMO1055ZM401 maintains cell aggregation and the intracellular cyclic di-GMP concentrations to a greater extent (Cao, Yang et al 2022, Li, Xia et al 2023. The conservation of alanine at position 526 in subclass ZMO1055 GGDEF-EAL domain proteins indicates that alanine is important for functionality of the EAL domain.…”
Section: Amino Acids At Position 526 Differentially Affect the Appare...supporting
confidence: 72%
“…Leucine, isoleucine and methionine are all non-polar amino acid and have similar size of side chain. Substantial DGC activity of ZMO0919 and ZMO1365 has been observed as predicted (Li, Xia et al 2023).…”
Section: Initial Characterisation Of the Ggdef/eal Domain Proteins Of...supporting
confidence: 64%
See 3 more Smart Citations